Nurse Anesthetist-Performed PICC Insertion: A Prospective Longitudinal Study in a Norwegian Hospital - Ann-Chatrin Linqvist Leonardsen; Ellen Marie Lunde; Mona Sand Andersen (SAGE Open Nursing)
Introduction The majority of hospitalized patients require vascular access for intravenous medical treatment. A peripherally inserted central catheter (PICC) may be indicated for long-term treatment. In many Norwegian hospitals, this is a nurse anesthetist-led initiative. Objective The aim of this study was to examine the use of PICCs from insertion to completed treatment and to assess potential risk factors for the development of catheter-related complications. Methods A quantitative prospective, longitudinal design was used. Data were collected via electronic patient records, as well as through telephone surveys with patients every fourth week until the catheter was discontinued. The Statistical Package for the Social Sciences version 28 was used for analysis. Results In total, 401 PICCs were included. The primary indications were antibiotic treatment ( n  = 272), nutrition ( n  = 46), or chemotherapy ( n  = 42). A total of 163 PICCs were used for a period of over 30 days. Overall, 41 catheter-related complications were identified through patient records. Erythema at the insertion site ( n  = 12) was the most common complication, and the most severe complications were deep venous thrombosis ( n  = 5) and confirmed catheter-related infection ( n  = 4). After 4 weeks, 12 patients reported complications, with pain/numbness ( n  = 4) being the most frequent. The study demonstrated no statistically significant covariation between the occurrence of complications and age, length of time the catheter was in use, primary indication, venous diameter, or the number of insertion attempts. Conclusion The study showed a low incidence of severe PICC-related complications. Peripherally inserted central catheters were inserted and used according to local guidelines. The study indicates that nurse anesthetists’ knowledge and experience can be utilized in the future selection and insertion of vascular access for patients, as well as in training and education on PICCs.